Tastes in landscapes - Colfer, C.J.P. (2003)
People have tastes in landscapes. This paper provides examples of different groups’ with lanscape tastes. It discusses, for instance, the Javanese preference for symmetry vis-à-vis the dayak’s appreciation of wildness, the ecologists’ enjoyment of natural chaos compared to the plantation specialist’s preference for tidy rows. Such tastes----under-recognized and under-acknowledged as they are, actually have important roles in many debates that rage and decisions that are made about land use.